Management of pediatric benign ovarian tumors in England and Egypt: A comparative study - Ahmed Elgendy; Bhanumathi Lakshminarayanan; Ahmed Elrouby; Mahmoud Mostafa; Mohamed Abouelmagd Salem; Kerry Turner; Ahmed Khairi; Roly Squire; Sherif M K. Shehata; Sameh Shehata; Mark Powis (Wolters Kluwer Medknow Publications, 2020)
Aim of the Study: We aimed to compare the management of pediatric benign ovarian tumors between an English center and three Egyptian institutions. Materials and Methods: This was a retrospective review of all children presenting with benign ovarian tumors between January 2014 and January 2019. A standardized dataset was used to compare between both sides. Results: Eighty-nine patients were included (54 English and 35 Egyptians). Median age at diagnosis in England was 13 years (2-16y), while in Egypt it was 7 years (9m-16y) with P =0.001. Mature teratomas or dermoid cysts were the most common findings in England and Egypt; 75.9% and 82.8% of cases, respectively. The presentation with an acute abdomen represented 27.8% of English and 28.6% of Egyptian patients. Incidentally diagnosed lesions constituted 15% of English patients, whereas none of the Egyptian cases were discovered incidentally. There were variations in diagnostic imaging; England: Ultrasound (USS) (54), magnetic resonance imaging (MRI) (37), and computed tomography (CT) (only one)-Egypt: USS (35), CT (17), and MRI (only one). Minimally invasive surgery (MIS) was performed in 15% of English and 23% of Egyptian patients (P = 0.334). Ovarian-sparing surgery (OSS) was performed in: England 35%, Egypt 37%; P = 0.851. OSS was performed using MIS in 87.5% (7/8) of English patients and 100% (8/8) of Egyptians. Patients presented as emergencies generally had open oophorectomies: England; 86.7% open and 80% oophorectomy-Egypt; 100% open and 90% oophorectomy. Recurrences or metachronous disease occurred in 5.6% of English and 5.7% of Egyptian patients. Conclusions: There were no significant differences regarding surgical management, tumor pathology, and recurrence or metachronous disease. However, age, incidental diagnosis, and imaging modalities showed notable differences. MIS was correlated with ovarian preservation, whereas emergency surgery generally resulted in open oophorectomy.